Enhancing bovine immune, antioxidant and anti-inflammatory responses with vitamins, rumen-protected amino acids, and trace minerals to prevent periparturient mastitis - Khan, Muhammad Zahoor; Huang, Bingjian; Kou, Xiyan; Chen, Yinghui; Liang, Huili; Ullah, Qudrat; Khan, Ibrar Muhammad; Khan, Adnan; Chai, Wenqiong; Wang, Changfa (Frontiers in Immunology, 2024)
Mastitis, the inflammatory condition of mammary glands, has been closely associated with immune suppression and imbalances between antioxidants and free radicals in cattle. During the periparturient period, dairy cows experience negative energy balance (NEB) due to metabolic stress, leading to elevated oxidative stress and compromised immunity. The resulting abnormal regulation of reactive oxygen species (ROS) and reactive nitrogen species (RNS), along with increased nonesterified fatty acids (NEFA) and β-hydroxybutyric acid (BHBA) are the key factors associated with suppressed immunity thereby increases susceptibility of dairy cattle to infections, including mastitis.Metabolic diseases such as ketosis and hypocalcemia indirectly contribute to mastitis vulnerability, exacerbated by compromised immune function and exposure to physical injuries. Oxidative stress, arising from disrupted balance between ROS generation and antioxidant availability during pregnancy and calving, further contributes to mastitis susceptibility. Metabolic stress, marked by excessive lipid mobilization, exacerbates immune depression and oxidative stress. These factors collectively compromise animal health, productive efficiency, and udder health during periparturient phases. Numerous studies have investigated nutrition-based strategies to counter these challenges. Specifically, amino acids, trace minerals, and vitamins have emerged as crucial contributors to udder health. This review comprehensively examines their roles in promoting udder health during the periparturient phase. Trace minerals like copper, selenium, and calcium, as well as vitamins; have demonstrated significant impacts on immune regulation and antioxidant defense. Vitamin B12 and vitamin E have shown promise in improving metabolic function and reducing oxidative stress followed by enhanced immunity. Additionally, amino acids play a pivotal role in maintaining cellular oxidative balance through their involvement in vital biosynthesis pathways. In conclusion, addressing periparturient mastitis requires a holistic understanding of the interplay between metabolic stress, immune regulation, and oxidative balance. The supplementation of essential amino acids, trace minerals, and vitamins emerges as a promising avenue to enhance udder health and overall productivity during this critical phase. This comprehensive review underscores the potential of nutritional interventions in mitigating periparturient bovine mastitis and lays the foundation for future research in this domain.